Fiqh dan Negara: Dinamika Penerapan Sanksi Hukuman Zina di Aceh - Nairazi, Nairazi; Akmal, Akmal; Ferizal, Indis; Manoppo, Feni Riana (IAIN Langsa, 2024)
The formalization of Islamic criminal law in Aceh until now is still reaping debates, one of the debates that arises regarding the proposed stoning penalty for adultery offenders. The debate arises because the Qanun Jinayat that regulates adultery is not like what is regulated in Islamic law. This led to various arguments that the qanun was made not serious and full of ruling interests. This research departs from the important question of why the specific legal sanctions for adultery offenders in Qanun Jinayat do not differentiate between muhsan and ghairu muhsan adulterers. Doctrinal method is used in this research to see the legal aspects of adultery regulated in Qanun Jinayat, the approach used is legislation and legal politics. This paper argues that the application of stoning law for muhsan adulterers can be enforced depending on the government agreement. When viewed from a legal aspect, stoning punishment cannot be applied in Aceh, because Aceh is part of the Indonesian government which has legal norms and values in law enforcement. Stoning is a form of death penalty that involves pain for the perpetrator which is considered by human rights as torture. In the Indonesian criminal law context, the death penalty is a severe criminal legal sanction that can be applied to the perpetrator if his actions are classified as serious crimes. In Islam, the death penalty can be applied to those who take the lives of others. This shows that legally and politically, stoning is difficult to enforce in Aceh. However, stoning punishment can be enforced by being equated to castration punishment as a form of law enforcement or exiled in a remote place as a form of providing a deterrent effect for the perpetrator.